2019
DOI: 10.1002/cncr.31930
|View full text |Cite
|
Sign up to set email alerts
|

Distinct genome‐wide methylation patterns in sporadic and hereditary nonfunctioning pancreatic neuroendocrine tumors

Abstract: BACKGROUND: Aberrant methylation is a known cause of cancer initiation and/or progression. There are scant data on the genome-wide methylation pattern of nonfunctioning pancreatic neuroendocrine tumors (NFPanNETs) and sporadic and hereditary NFPanNETs. METHODS: Thirty-three tissue samples were analyzed: they included samples from sporadic (n = 9), von Hippel-Lindau (VHL)-related (n = 10), and multiple endocrine neoplasia type 1 (MEN1)-related NFPanNETs (n = 10) as well as normal islet cells (n = 4) for compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 55 publications
1
37
0
Order By: Relevance
“…In addition, also other epigenetically regulated processes such as chromatin and chromosome condensation are situated in the top GO categories, which again supports the importance of epigenetic deregulation in PNENs. Platelet-related pathways were also enriched, which has been observed previously by Tirosh et al in familial PNENs [12]. It has been shown that PNEN patients with tumor-associated platelets have a worse prognosis, possibly through modulation of the platelet behavior [38].…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In addition, also other epigenetically regulated processes such as chromatin and chromosome condensation are situated in the top GO categories, which again supports the importance of epigenetic deregulation in PNENs. Platelet-related pathways were also enriched, which has been observed previously by Tirosh et al in familial PNENs [12]. It has been shown that PNEN patients with tumor-associated platelets have a worse prognosis, possibly through modulation of the platelet behavior [38].…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, high portions of hypermethylated DMPs were found in the gene body (22.5%) and the 5'UTR (22.1%) and gene body methylation has been described to be able to increase the gene expression, for example, of metabolic genes or oncogenes [31]. Gene set enrichment analysis has highlighted the MAPK pathway as a possibly important pathway in PNENs, which has been suggested before based on genetic and epigenetic alterations [9,12,32,33]. Cross-talk between the PI3K/AKT/mTOR pathway and the MAPK pathway has been described in neuroendocrine neoplasms and other cancer types, and dual inhibition of these pathways has been shown to be more effective in in vitro and in vivo neuroendocrine neoplasm models [34][35][36].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…DNA hypermethylation has an important role in PanNET tumorigenesis and should be further studied to potentially identify novel therapeutic targets (Conemans et al 2018, Tirosh et al 2019. Additional inquiries included the exploration of possible immunotherapybased interventions to prevent metastases or PanNET.…”
Section: Discussionmentioning
confidence: 99%
“…From our study, although some of these genes methylation (such as S0 × 17 and RAP1GAP) was previously reported in MDS [31,32], the majority of them were unknown so far. Interestingly, some of them were reported to be methylated in other blood cancers or solid tumors, such as HOXD11, GBX2, CRMP1, RBM47, NHLRC1, WNT2, TUSC3, NRG1, TSPYL5, CNTFR, NR4A3, PHOX2A, KCNA5, PTGDR, HS3ST2, CLDN7, CPT1C, and NKX2-4 [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48]. Based on these ndings, we further selected the unreported hypermethylated genes with potential roles involved in MDS progression for further validation.…”
Section: Discussionmentioning
confidence: 99%